On the account of the free surface motion in the calculation of the hydrodynamic loadings on wedges - Tudoran, Viktoriya (Видавництво Львівської політехніки, 2013)
A nonlinear numerical simulation method for predicting wave loads on two-dimensional frame sections that entries the water with accounting of the free surface motion for determination of the hygdrodynamic loads has been developed. A complex boundary elements method and the mixed Euler-Lagrangian method are employed for the analysis of the problems. An attention is focused on the computational description of the jet stream without breaking the physics of free surface motion. Hydrodynamic force impacts the submerging wedges with different deadrise angles has been calculated using the developed software based on this method.
Keywords: two-dimensional water flow simulation; free surface motion; hydrodynamic loads; Euler-Lagragian scheme; complex boundary elements method; jet stream; frame section; strip theory